Performance study of centrifugal pump using different foot - valves and pipes - JYOTHY PADMAKUMAR; Kailas K. P; Litha S; Er. Suseela P (Guide) (Tavanur 1996 Department of Irrigation and Drainage Engineering)
Performance study of centrifugal pump using different foot - valves and pipes
Performance study of centrifugal pump using different foot - valves and pipes